A case report of severe hyponatraemia secondary to enalapril and olanzapine. (24th December 2016) - Ng, Yen Ping; Ooi, Guat See; Balasubramanian, Ganesh Pandian; Tan, Winnie Sze Hui
Abstract: Background: Olanzapine is a commonly used atypical antipsychotic in the management of schizophrenia. Its well‐known adverse effects include sedation, weight gain and metabolic adverse effects. Enalapril is widely used as an antihypertensive with the known adverse drug effect of hyperkalaemia. Aims: To report a very rare adverse effect of enalapril and olanzapine induced severe hyponatraemia. Clinical details: A 56‐year‐old lady was admitted to the hospital suffering from severe lethargy, decreased oral intake, and a decreased level of consciousness. She had been taking olanzapine 10 mg once at night for the past one and a half years and enalapril 5 mg twice daily for the past three years. Laboratory investigations revealed a plasma sodium level of 110 mmol/L, blood osmolality of 244 mosm/kg and urine osmolality of 512 mosm/kg. A diagnosis of SIADH (syndrome of inappropriate diuretic hormone) was made. Enalapril and olanzapine were suspected as causative agents as there was no other apparent cause of SIADH identified. Outcome: Patient was treated with normal saline in the ward and her plasma sodium level rose to 130 mmol/L. Conclusion: Enalapril or olanzapine induced hyponatraemia is extremely rare. However, healthcare professionals should be aware that patients being treated with enalapril or olanzapine alone or in combination can develop hyponatraemia in addition to their known metabolic adverse effects. Sodium level monitoring is necessary if patient develop symptoms suggestive of hyponatraemia.